Expanding coastal urban and industrial seascape in the Great Barrier Reef World Heritage Area: Critical need for coordinated planning and policy. (July 2015) - Waltham, Nathan J; Sheaves, Marcus
Abstract: Coastal freshwater and tidal wetland habitats are being transformed as a result of increasing demand for commercial, residential and tourism activities. The consequence is a habitat seascape complex, comprising a mosaic of natural and engineered coastal features. This study used the freely available mapping tool (Google Earth) to define the extent of coastal engineering structures in the Great Barrier Reef World Heritage Area (GBR; Australia), a marine ecosystem of global biodiversity and cultural significance. Continuing threats to the heritage estate concomitant with expanding urban and industrial developments has raised concerns directed at the future conservation and resilience of the reef ecosystems, along with maintaining expected human lifestyles and livelihoods it provides. The data here shows that break walls and pontoons/jetties dominate development, contributing to approximately 10% (equivalent) of the coastline linear length. Most (60%) development occurs along the coastline or within the first few kilometres upstream along estuaries. While conservation and protection of natural coastal habitats is still preferred for the objective of fisheries production and biodiversity, managers must consider seascape implication/benefits more broadly when approving new marine infrastructure rather than a case-by-case approach which further contributes to an ad hoc mosaic seascape of natural and engineered habitats. Not only within the GBR heritage estate, but more broadly, coastal managers need to regard wider seascape connectivity processes during the assessment of any new development. There is an urgent need for policy and planning instrument reform that is inclusive of accumulative impacts of urban and industrial development in this heritage estate. Opportunities to include eco-friendly (green engineering) solutions, in the repair and revitalisation of existing artificial structures, is necessary in any new proposed urban and industrial development and expansion.